2001
DOI: 10.1590/s0101-81752001000500002
|View full text |Cite
|
Sign up to set email alerts
|

Moscas ectoparasitas (Diptera, Hippoboscoidea, Nycteribiidae) de morcegos (Mammalia, Chiroptera) do Estado do Paraná, Brasil. I. Basilia, taxonomia e chave pictórica para as espécies

Abstract: ABSTRACT. Batflies (Diptera, Hippoboscoidea, Nycteribiidae) Guimarães, 1946. The male 01' B. juquiensis Guimarães is eharacterized. Basilia lindolphoi sp. n. is described. Pictorial keys to species are presented, and female abdomens are illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 5 publications
(5 reference statements)
2
22
0
4
Order By: Relevance
“…S. mirabilis is found from Mexico to Paraguay and, in Brazil, its presence has been recorded in the states of Pará (PA), Paraná (PR), Rio de Janeiro and FD (Graciolli et al 2008). In a broad study conducted in Paraguay, Dick and Gettinger 2005 had found that the specificity of Strehad found that the specificity of Stre- (Guerrero 1996, Graciolli & Carvalho 2001a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. mirabilis is found from Mexico to Paraguay and, in Brazil, its presence has been recorded in the states of Pará (PA), Paraná (PR), Rio de Janeiro and FD (Graciolli et al 2008). In a broad study conducted in Paraguay, Dick and Gettinger 2005 had found that the specificity of Strehad found that the specificity of Stre- (Guerrero 1996, Graciolli & Carvalho 2001a.…”
Section: Discussionmentioning
confidence: 99%
“…All ectoparasites observed on the bats were removed with forceps and preserved in 70% ethanol. The species of the bat flies were determined by using keys for Neotropical bat flies , Wenzel 1976, Guerrero 1993, 1994a, b, 1995a, b, 1996, 1998, Graciolli & Carvalho 2001a, b, Miller & Tschapka 2005 Data analysis -We calculated the prevalence, intensity and mean intensity of infestation by parasites with the Quantitative Parasitology v3.0 software (Rózsa et al 2000). Terminology relating to measurements of parasite variables as well as parasitism rate and relationships were as described in Bush et al (1997).…”
mentioning
confidence: 99%
“…The species ranges from Mexico to southern Brazil (Guerrero 1994, Graciolli & Carvalho 2001, and is an exclusive parasite of C. perspicillata (Wenzel 1976, Guerrero 1994 (Dias et al 2009), which was so far the typical host of this parasite (Wenzel 1976, Guerrero 1996.…”
Section: Methodsmentioning
confidence: 99%
“…Graciolli et al 2008, Graciolli & Rui, 2001. A total of 70 streblid species have been recorded in Brazil, although the vast majority of the data are from the southern and central regions of the country (Graciolli & Carvalho 2001, Aguiar et al 2006, Dias et al 2009), whereas few faunistic surveys have been conducted in the Northeast, where only 26 streblid species have been reported. Most of these species (22) were recorded during a long-term survey in Maranhão state (Dias et al 2009), while Rios et al (2008) registered two other species in Bahia state.…”
Section: Introductionmentioning
confidence: 99%
“…Pela facilidade de captura e de manipulação do hospedeiro e a melhor visualização dos dípteros sobre o corpo de morcegos, vários artigos têm sido publicados sobre a ocorrência de dípteros ectoparasitos de morcegos no Brasil (por exemplo, Dias et al, 2009;Graciolli & Bianconi, 2007;Graciolli et al, 2010;Lourenço & Esbérard, 2011;Aguiar & Antonini, 2011). Além disso, artigos recentes sobre a taxonomia dessas famílias de dípteros ectoparasitos de morcegos têm facilitado a identificação dos gêneros e das espécies e despertado o interesse de estudantes e pesquisadores (Dick & Miller, 2010;Graciolli, 2004;Graciolli & Azevedo, 2011;Graciolli & Carvalho, 2001a;2001b;Graciolli & Dick, 2012;Graciolli & Moura, 2005), enquanto importantes contribuições sobre a taxonomia de hipoboscídeos neotropicais são mais escassos (Graciolli & Carvalho, 2003;, sendo os mais importantes publicados a mais 40 anos (Bequaert, 1954;Maa, 1969;Peterson & Maa, 1970), por exemplo.…”
Section: Lipoptena Mazamae (Rondani 1878) Ozotocerosunclassified